maxLik: A package for maximum likelihood estimation in R - Henningsen, Arne; Toomet, Ott (Computational statistics, 2011)
This paper describes the package maxLik for the statistical environment R. The package is essentially a unified wrapper interface to various optimization routines, offering easy access to likelihood-specific features like standard errors or information matrix equality (BHHH method). More advanced features of the optimization algorithms, such as forcing the value of a particular parameter to be fixed, are also supported.